Pre-operative nomogram predicting malignant potential in the patients with intraductal papillary mucinous neoplasm of the pancreas: focused on imaging features based on revised international guideline. - Hwang, Jeong Ah; Choi, Seo-Youn; Lee, Ji Eun; Kim, Seung Soo; Lee, Sunyoung; Moon, Ji Yoon; Heo, Nam Hun (European Radiology, 2020)
Objective: To clarify the pre-operative imaging and clinical features differentiating malignant from benign intraductal papillary mucinous neoplasm (IPMN) of the pancreas and develop a nomogram for estimating the individualized risk of malignant IPMN.Methods: One hundred twenty-six patients with IPMN (72 benign and 54 malignant) who underwent pre-operative contrast-enhanced CT or MRI from 2010 to 2018 were retrospectively evaluated in two tertiary institutions. All lesions were pathologically proven by surgery or biopsy. Significant imaging and clinical findings for malignancy were assessed by univariate and multivariable logistic regression analyses. Based on the significant variables in the multivariable analysis, we developed a nomogram to predict malignant potential in patients with IPMNs, and the area under the receiver operating characteristic curve (AUC) was used to assess the diagnostic value.Results: Multivariable analysis revealed that enhancing mural nodule ≥ 5 mm (odds ratio (OR), 48.30; 95% confidence interval (CI), 11.69-199.49), increased serum carbohydrate antigen 19-9 (CA19-9) (OR, 8.69; 95% CI, 2.04-36.92), main pancreatic duct (MPD) diameter ≥ 10 mm (OR, 6.34; 95% CI, 1.21-33.30), and acute pancreatitis (OR, 4.77; 95% CI, 1.12-20.36) were independent significant parameters to predict malignant IPMN. Among them, enhancing mural nodule ≥ 5 mm showed the highest OR and predictor point on the nomogram. The AUC for the nomogram was 0.955 (95% CI, 0.903-0.984).Conclusions: Pre-operative imaging findings could aid in predicting malignant potential of IPMN using the significant findings of enhancing mural nodule ≥ 5 mm, increased serum CA19-9, MPD diameter ≥ 10 mm, and acute pancreatitis.Key Points: • Among pre-operative imaging and clinical features, enhancing mural nodule ≥ 5 mm, increased serum CA19-9, main pancreatic duct diameter ≥ 10 mm, and acute pancreatitis were independent significant parameters to predict malignant IPMN. • Enhancing mural nodule ≥ 5 mm was a single predictor for malignant IPMN, with the highest diagnostic values compared to other significant parameters. • A constructed nomogram using these parameters could aid in predicting malignant potential in patients with IPMN of the pancreas.